Vulva Hygiene Analysis Using Betel Leaf Decoction in Puerperal Period with Healing of Perineal Wounds in BPS Ria Mulya p, sst., M .kes in Katerungan village, Krian Sidoarjo - isty isty istianah; FENTI DWI FIBRIANA (Bina Sehat Press. Departement Research and Community Engagement Bina Sehat PPNI Institute of Health Science, Indonesia, 2018)
Vulva hygiene in the treatment of birth canal injuries consist of 2 types, there were using antiseptics and not using antiseptics, which is used traditional treatments that use betel leaves. Treatment of birth canal injuries using betel leaves by boiling and using the water for vulva hygiene or cleaning the wound of the birth canal. Based on the survey conducted in March 2018 on 10 post partum mothers who visited the BPS Ria Mulya P, SST., M.Kes. on Katerungan Krian Sidoarjo the researchers observed and filled out observation sheets on 10 respondents that 10 postpartum mothers who used stew betel leaves, 7 postpartum mothers (70%) Healing wounds quickly and 3 postpartum mothers (30%) Healing of his wounds slowly. This condition that the number of postpartum mothers who heal their wounds quickly using betel leaf decoction. The method of this study is used longitudional analytic. The population was 30 postpartum mothers who visited clinic. Samples were taken were 30 respondents (postpartum mothers with perineal suture wounds using betel leaf decoction) using the Proposive sample technique. Data collection using observation sheets then the data tabulated and analyzed by chi square test. Based on the results of the calculation of the chi square test, the result of the Pvalue <Î± is 0.007 <0.005. This shows that there is an effect of vulva hygiene using betel leaf decoction during childbirth with perineal wound healing. The conclusion of this study is the decoction of betel leaf able to accelerate the process of healing perineal wounds during childbirth. The results of this study are still not perfect, and the ability of research is limited, for the next researcher more numbers of respondents are prepared so that the generalization can be expanded. Keywords: Vulva Hygiene, betel leaf decoction, Perineum Wound Healing.